A new shrew mole species of the genus Uropsilus (Eulipotyphla: Talpidae) from northwestern Vietnam - Bui, Hai Tuan; Okabe, Shinya; Le, Linh Tu Hoang; Nguyen, Ngan Thi; Motokawa, Masaharu (Zootaxa, 2023)
A new medium-sized shrew mole species of the genus Uropsilus from Mount Fansipan, Hoang Lien National Park, Lao Cai Province, northwestern Vietnam is described based on morphological and molecular differences. Uropsilus fansipanensis sp. nov. is distinguished from the other Uropsilus species by the combination of the following features: the dorsum is lightly reddish-brown and venter is dark gray; the dark gray tail is long and slender, with a scattered white base and short bristle hairs; orbital process is oriented upwards posteriorly; lacrimal foramen is well developed and much larger than infraorbital foramen; the lower first premolar is approximately the same size as the lower third premolar. Genetic distances in terms of mitochondrial cytochrome b from other Uropsilus species presented pairwise divergences from 8.63 to 20.70%. To date, the new species is known to exist only in the type locality of Mt. Fansipan, a wet and cold temperate climate area with an upper montane forest at an elevation of approximately 2900 m, forming the southernmost distribution of the genus Uropsilus.